2021
DOI: 10.1007/s00238-021-01845-x
|View full text |Cite
|
Sign up to set email alerts
|

Complication after Aquafilling® gel-mediated augmentation mammoplasty—galactocele formation in a lactating woman: a case report and review of literature

Abstract: Augmentation mammoplasty using hydrogel fillers such as polyacrylamide gel (PAAG) or Aquafilling® has been performed commonly in some countries as an alternative to breast augmentation with saline or silicone implants. However, the safety of this procedure remains controversial, and many complications associated with the use of large-volume hydrogel injection have been reported in recent years. We present the case of a 33-year-old woman with a history of bilateral Aquafilling® injection augmentation mammoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
(69 reference statements)
0
11
1
2
Order By: Relevance
“…One patient (case 1) showed invasive ductal carcinoma, but the relationship with the filler injection is unclear. Common complications reported in other studies, such as migration, masses, and infection, were not found in our cases, and studies also vary in terms of the interval until symptom onset, which was 13.2 years in our study, but less than 10 years in others [3,5,7,8].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…One patient (case 1) showed invasive ductal carcinoma, but the relationship with the filler injection is unclear. Common complications reported in other studies, such as migration, masses, and infection, were not found in our cases, and studies also vary in terms of the interval until symptom onset, which was 13.2 years in our study, but less than 10 years in others [3,5,7,8].…”
Section: Discussioncontrasting
confidence: 48%
“…Although the use of fillers for body contouring, including breast augmentation, has not been approved by the Food and Drug Administration, fillers (e.g., hyaluronic acid, copolyamide, and polyacrylamide) have been and are still being used for breast augmentation [4,6,7]. The use of a PAAG filler (Amazingel) was approved by the Chinese Food and Drug Administration; however, it was banned in 2006 because of associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of the 16 included studies reported complications, 6 , 7 , 9 , 10 , 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 and one study solely described a method of using Aquafilling to fill deformities after breast augmentation with implants. 8 …”
Section: Resultsmentioning
confidence: 99%
“…All in all, 196 women who had injections with dermal fillers containing copolyamide were included in this systematic review. The majority ( n = 191) had injections with Aquafilling/Los Deline, 6 , 7 , 8 , 10 , 11 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 and one study reported 5 women who had injections with Aqualift/Activegel 9 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 AQUAlift/Aquafilling gel is not FDA approved. 10 There are numerous case reports 9 , 11-14 regarding complications related to Aquafilling breast augmentation. The most frequently reported complications include filler migration, late hematomas, skin fistulae, aspecific inflammatory symptoms, breast swelling, and deformity.…”
Section: Discussionmentioning
confidence: 99%